ANÁLISIS PRELIMINAR DE LA ICTIOFAUNA DE ALTO GUAYACÁN (COSTA RICA) CON BASE EN LOS OTOLITOS. FORMACIÓN USCARI (MIOCENO SUPERIOR-PLIOCENO INFERIOR) - Laurito M., César A. (2011)
The beds of the well-known fossil mollusc locality of Alto Guayacan contain a rich selachianfauna and an important otolith assemblage. This assemblage illustrates conditions of the outer shelf zone, withnormal salinity and direct conection with the open ocean, near mesopelagic zone. The fossil record recovered,comprises: 4 orders, 7 families, 10 genera and at least 18 species. Some genera were reported previously for ot-hers geological formations in the Caribbean Region, like Gatun Fm. in the Panama Canal Zone or the Guraboand Mao Formations in the Pliocene of the Dominican Republic.